NILAI-NILAI PSIKOLOGI PENDIDIKAN DALAM AL-QUR’AN - Moh. Irmawan Jauhari; M. Luqman Hakim (Piwulang: Jurnal Pendidikan Agama Islam, 2020)
Humans in the era of globalization have a level of mental vulnerability that is easily cracked and destroyed. Too much competition and the influence of information technology presents more complex problems. It is not uncommon for modern humans to flee to actions that are detrimental to themselves and society. Because they feel that their psychological burden is so heavy and cannot be borne by themselves. The Qur'an provides an understanding of human beings complete with their potential. In this case, also includes the psychological potential given by God so that humans are able to manage the universe. Understanding of the psychic potential of humans is important so that humans do not always hunt for what appears, but also provide inner satisfaction so that physical and psychological balance occurs. AbstrakManusia dalam era globalisasi memiliki tingkat kerentanan jiwa yang mudah retak dan hancur. Persaingan yang sedemikian hebat serta pengaruh teknologi informatika menghadirkan persoalan yang lebih kompleks. Tidak jarang kemudian manusia modern melarikan diri kepada perbuatan-perbuatan yang justru merugikan dirinya sendiri serta masyarakat. Sebab mereka merasa bahwa apa yang menjadi beban psikisnya sedemikian berat dan tidak bisa ditanggung sendiri. Al-Qur’an memberikan pemahaman mengenai manusia lengkap dengan potensi yang dimiliki. Dalam hal ini juga termasuk potensi psikis yang diberikan Allah agar manusia mampu mengelola alam semesta. Pemahaman potensi psikis manusia ini penting agar manusia tidak selalu memburu apa yang nampak, akan tetapi juga memberikan kepuasan batin agar terjadi keseimbangan jasmani dan psikisnya.